Effect of Dipping Time of Filter Paper using SiO2-Chitosan Nanocomposite on Contact Angle for Water and Oil Separation - Jasmine, Alifa; Ratnawulan, Ratnawulan; Darvina, Yenni; Hidayat, Rahmat (Journal of Experimental and Applied Physics, 2025)
The introduction of organic compound enriched wastewater into aquatic environments can cause a drop in dissolved oxygen, with significant consequences for microorganisms living in such environments. Ultimately, this problem jeopardizes the survival of higher trophic level animals in such environments. In recent times, new membrane technology development has received a lot of attraction, with membrane processes becoming increasingly utilized in oily wastewater separation processes. Membrane processes have proven effective in the removal of oils in water during such separation processes. An effective membrane for such a purpose is a silica composite membrane with a hydrophobic property, synthesized with a cellulose paper substrate and a silica of rice husks for use in creating an active membrane layer. In one part of a current investigation, dyeing duration impact was considered through changing immersion times for SiO2-chitosan nanocomposite coated filter paper for 5, 10, 15, and 20 minutes. In such a study, contact angles for 5, 10, 15, and 20-minutes' immersion times have been measured and documented at 94.35°, 98.53°, 101.04°, and 104.34°, respectively. In addition, an evaluation was performed to assess water and oil separation effectiveness with cellulose paper coated with SiO2/Chitosan composite, with efficiencies of 80%, 85%, 87.5%, and 90%, respectively, documented for such processes.